A new paradigm for cancer immunotherapy: targeting immunogenic cell death-related noncoding RNA - Sun, Guojuan; He, Ling (Frontiers in Immunology, 2025)
Cancer immunotherapy has shown significant potential in treating several malignancies by stimulating the host immune system to recognize and attack cancer cells. Immunogenic cell death (ICD) can amplify the antitumor immune responses and reverse the immunosuppressive tumor microenvironment, thus increasing the sensitivity of cancer immunotherapy. In recent years, noncoding RNAs (ncRNAs) have emerged as key regulatory factors in ICD and oncologic immunity. Accordingly, ICD-related ncRNAs hold promise as novel therapeutic targets for optimizing the efficacy of cancer immunotherapy. However, the immunomodulatory properties of ICD-related ncRNAs have not yet been comprehensively summarized. Hence, we summarize the current knowledge on ncRNAs involved in ICD and their potential roles in cancer immunotherapy in this review. It deepens our understanding of ncRNAs associated with ICD and provides a new strategy to enhance cancer immunotherapy by specifically targeting the ICD-related ncRNAs.